Alcohol and pH Detectors Based Internet of Thing for Hand Sanitizer - Feri Adriyanto; Geovani Rahmad Illahi; Hayyan Yusuf; Diah Anggi Munika; Yuki Martha Anggraini; Hibatul Wafi Ah Fahrudin (Universitas Sebelas Maret (UNS), 2021)
Alcohol and pH levels in hand sanitizer are two things that need to be considered. The amount of alcohol content affects the level of effectiveness in killing germs, while the pH level is a factor that indicates whether the liquid is safe for human skin or not. HANDSIOT is a device to measure alcohol levels and pH in hand sanitizers. HANDSIOT is operated by testing the hand sanitizer liquid in the liquid container at the bottom. This device is made to be able to take measurements effectively and can monitor the measurement results in real-time using a smartphone. Gas chromatography and electrolysis methods were implemented using the MQ-3 gas sensor and the SEN0161 pH sensor. The gas chromatography method is used as a method of measuring alcohol content based on the evaporation of the alcohol. While the electrolysis method is used to measure the pH degree by measuring the amount of current flowing using two electrodes. In testing the accuracy of this tool by comparing the readings on the tool with an alcohol meter and also a pH sensor that is already available on the market